PERBANDINGAN NILAI KARAKTERISTIK MARSHALL UNTUK CAMPURAN AC-WC MENGGUNAKAN QUARRY AKANUNU DAN QUARRY HERA - Bela, Krisantos (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
Asphalt Concrete - Wearing Course (AC-WC) is a road construction layer consisting of coarse aggregate, fine aggregate, filler, and hard asphalt. This material is mixed, laid, and compacted at specific temperatures to form a durable and strong road surface layer. Enhancing road resilience against various factors causing damage is essential to maintain transportation systems and ensure even economic growth across regions. In this context, it's important to compare the physical and mechanical characteristics of AC-WC mixtures using materials from Quarry Akanunu and Quarry Hera. The aim of this study is to assess the performance of AC-WC mixtures from both quarries using the standard Marshall 2 x 75 blows testing method. The research findings indicate that using an optimal asphalt content of 5.85% from Quarry Akanunu, there are differences in Marshall characteristics compared to mixtures using materials from Quarry Hera. At an asphalt content of 5.85% from Quarry Akanunu, the differences in stability values reached 67.28 kg, flow 0.13 mm, VIM (Void in the Mix) 0.31%, VMA (Void in Mineral Aggregate) 0.14%, VFB (Void Filled with Bitumen) 1.22%, and Marshall Quotient (MQ) 31.43 Kg/mm. Meanwhile, using an optimal asphalt content of 5.90% from Quarry Hera, the differences in stability values reached 69.90 kg, flow 0.15 mm, VIM 0.31%, VMA 0.14%, VFA 1.22%, and MQ 33.12 Kg/mm. From this analysis, Quarry Hera shows slightly better performance in terms of stability and other Marshall characteristics compared to Quarry Akanunu, although both mixtures meet the specifications of Bina Marga 2018 revision 2.